Lip projection analysis in brachycephalic, dolichocephalic and mesocephalic individuals of a Mexican population. - Sánchez Meraz, Wulfrano; Arredondo Hérnandez, Raymundo; Avalos Sanchez, Diana; Mariel Murga, Humberto; Gutiérrez Cantu, Francisco Javier; Mariel Cárdenas, Jairo (Investigación Clínica, 2016)
Ver Resumen PDf.